Diagnosing gastric volvulus in chest X-ray: report of three cases. Issue 7 (16th July 2020) - Pandit, Narendra; Kumar, Abhijeet; Yadav, Tek Narayan; Irfan, Qamar Alam; Gautam, Sujan; Awale, Laligen
Abstract: Gastric volvulus is a rare abnormal rotation of the stomach along its axis. It is a surgical emergency, hence requires prompt diagnosis and treatment to prevent life-threatening gangrenous changes. Hence, a high index of suspicion is required in any patients presenting with an acute abdomen in emergency. The entity can present acutely with pain abdomen and vomiting, or as chronic with non-specific symptoms. Chest X-ray findings to diagnose it may be overlooked in patients with acute abdomen. Here, we report three patients with gastric volvulus, where the diagnosis was based on the chest X-ray findings, confirmed with computed tomography, and managed successfully with surgery.